2021
DOI: 10.1038/s41467-021-26560-w
|View full text |Cite
|
Sign up to set email alerts
|

Partially overlapping spatial environments trigger reinstatement in hippocampus and schema representations in prefrontal cortex

Abstract: When we remember a city that we have visited, we retrieve places related to finding our goal but also non-target locations within this environment. Yet, understanding how the human brain implements the neural computations underlying holistic retrieval remains unsolved, particularly for shared aspects of environments. Here, human participants learned and retrieved details from three partially overlapping environments while undergoing high-resolution functional magnetic resonance imaging (fMRI). Our findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 108 publications
5
40
1
Order By: Relevance
“…Evidence in humans generally corroborates the research in animal models, suggesting that, as a whole, the HC supports episodic memory by binding together information about items and the context in which they were encountered (Davachi, 2006; Eacott & Gaffan, 2005; Eichenbaum et al, 2007; O’Keefe & Nadel, 1978; Ranganath, 2010; Y. Zheng et al, 2021). At present, however, there is little known about the roles of different hippocampal subfields in item-context binding.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Evidence in humans generally corroborates the research in animal models, suggesting that, as a whole, the HC supports episodic memory by binding together information about items and the context in which they were encountered (Davachi, 2006; Eacott & Gaffan, 2005; Eichenbaum et al, 2007; O’Keefe & Nadel, 1978; Ranganath, 2010; Y. Zheng et al, 2021). At present, however, there is little known about the roles of different hippocampal subfields in item-context binding.…”
Section: Introductionsupporting
confidence: 57%
“…Computational models (Marr, 1971; for a non-Hebbian instantiation, see Y. Zheng et al, 2021) propose that the combination of sparse coding in DG and the dense recurrent collaterals that make up the majority of the inputs to CA3 (Amaral & Witter, 1989) enable the hippocampus to retrieve or recover a memory trace given a noisy or incomplete retrieval cue (i.e., “pattern completion” (Marr, 1971; O’Reilly & McClelland, 1994; Yassa & Stark, 2011). A second factor that is key to understanding hippocampal function is that CA3 and DG are critical sites for binding of information about items and contexts (Knierim et al, 2006; Y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a previous study in which participants viewed first-person trajectories to real-world destinations found that representations of routes with overlapping sections were differentiated in the hippocampus following learning 20 . Another study observed differentiation of hippocampal patterns for landmarks that were common to multiple virtual cities 52 . By contrast, other studies found evidence of integration for items that share spatial and temporal context 58 and for objects located in geometrically similar positions across subspaces of segmented environments 59 .…”
Section: Introductionmentioning
confidence: 99%
“…Functional coupling between these regions during learning supports the initial formation of structured knowledge and predicts subsequent memory [42][43][44][45][46] . Over time, vmPFC abstracts and represents commonalities across episodes 25,47,48 , leading some to propose that structured representations are stored in this region [49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%